Exploring the thermodynamic criteria for responsive adsorption processes. Issue 19 (15th April 2019) - Evans, Jack D.; Krause, Simon; Kaskel, Stefan; Sweatman, Martin B.; Sarkisov, Lev
Abstract : A general thermodynamic model to investigate responsive adsorption processes in flexible porous materials. Abstract : We describe a general model to explore responsive adsorption processes in flexible porous materials. This model combines mean field formalism of the osmotic potential, classical density functional theory of adsorption in slit pore models and generic potential functions which represent the Helmholtz free energy landscape of a porous system. Using this model, we focus on recreating flexible adsorption phenomena observed in prototypical metal–organic frameworks, especially the recently discovered effect of negative gas adsorption (NGA). We identify the key characteristics required for the model to generate unusual adsorption processes and subsequently employ an extensive parametric study to outline conditions under which gate-opening and NGA are observed. This powerful approach will guide the design of responsive porous materials and the discovery of entirely new adsorption processes.